Positive Classroom Management (PCM): Integrated Classroom Management Training Program To Build A Conducive and Meaningful Learning Ecosystem In Grade XII In The Digital Era - Mesra, Romi; Neviyarni , Neviyarni; Mudjiran, Mudjiran (Laboratorium Program Studi Pendidikan Sosiologi Unima, 2024)
This study aims to develop a Positive Classroom Management (PCM) program as an integrative solution for managing digital-era classrooms, specifically focusing on grade XII students. The research addresses the challenges of maintaining student engagement, managing technology use, and supporting student well-being in contemporary educational settings. The study employs a qualitative approach through systematic literature review, analyzing 150 selected articles from 500 initial sources published between 2019-2024. Data collection utilized major academic databases including ERIC, Science Direct, JSTOR, and Google Scholar, with analysis conducted using NVivo 14 software for theme identification and meta-synthesis. Results reveal five key components of effective digital classroom management: digital behavior management systems, integrated communication platforms, student progress monitoring systems, virtual collaboration tools, and learning analytics dashboards. The study found that optimal implementation requires a 60:40 ratio of digital to direct interaction activities. The PCM program successfully increased student collaboration by 55% and parental involvement by 65%. Implementation challenges included infrastructure limitations, digital literacy gaps, and online engagement monitoring. The research demonstrates that integrating technology with traditional pedagogical approaches, while maintaining focus on student well-being, creates a more effective and supportive learning environment for grade XII students in the digital era.